Industrialisation, Finance and Urbanisation in Africa (2023)
This article investigates two key questions: what is the impact of industrialization on urbanization in Africa? And to what extent does financial development affect this industrialization–urbanization nexus? To elicit answers to these questions, data from 33 African countries over a period of 28 years were analyzed using a dynamic panel estimator. The findings showed that industrialization had positive and significant effects on urbanization. Further, the study shows that financial development had a positive effect on urbanization, although it lowers the positive effect of industrialization on urbanization. Hence, industrial policies, particularly those with marked job creation possibilities, should be accompanied by well-designed urban planning policies in order to sidestep the adverse socioeconomic consequences connected with the development of slums in urban areas.